2021
DOI: 10.1108/shr-11-2021-0053
|View full text |Cite
|
Sign up to set email alerts
|

How preferences for types of appreciation differ across employee age groups

Abstract: Purpose Organizational leaders and human resource professionals affirm that to have (and keep) an effective workforce, understanding one’s employees is critical. Thus, understanding the differences between employees of different age groups is important. Simultaneously, studies have demonstrated the significant positive impact appreciation has on the functioning of organizations. When team members feel truly valued, numerous positive benefits result, including lower staff turnover, less absenteeism, higher cust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Previous studies have also shown that the frequency of appreciation language preferences is essentially equivalent across gender (White, 2017), but that there are slight differences across age groups (White and George, 2022). Employees under the age of 30 prefer the language of Quality Time slightly more than their older colleagues, while older employees (60+ years old) valued Tangible Gifts less than their younger coworkers.…”
Section: Introductionmentioning
confidence: 94%
“…Previous studies have also shown that the frequency of appreciation language preferences is essentially equivalent across gender (White, 2017), but that there are slight differences across age groups (White and George, 2022). Employees under the age of 30 prefer the language of Quality Time slightly more than their older colleagues, while older employees (60+ years old) valued Tangible Gifts less than their younger coworkers.…”
Section: Introductionmentioning
confidence: 94%
“…Research (White, 2017) has shown that not everyone feels appreciated in the same ways and that differences in preferences occur across age groups (White, 2018; White and George, 2022) and occupational settings (White, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that individuals prefer to be shown appreciation in various ways (White, 2017). Additionally, differences in preferences occur across age groups (White, 2018a(White, , 2018bWhite and George, 2022), occupational settings (White, 2023a) and whether the employees work primarily remotely or onsite (White, 2021).…”
mentioning
confidence: 99%